Impact of online teaching and learning towards mental health of university students - Tuan Othman, Sharifah Izwan; Mohd. Johari, Mohammad Syamri; A. Rahman, Mohd. Darnalis; Baharun, Nurkhairul Bariyah; Darawi, Mohd. Nazif; Mukhtar, Firdaus (European Publisher, 2022)
The landscape of higher education has been changed from face-to-face mode to fully online teaching and learning (OTL) due to long practice of lockdown caused by COVID-19 pandemic which forced the education industry to adapt to the new norm of teaching and learning. This study aimed to determine the impact of online learning towards the mental health status of higher education students. Survey-based research was conducted using online Google Form questionnaires among University Selangor (UNISEL) students who already experienced OTL for at least one semester involving seven faculties. A total of 184 students were chosen and the mental health status of UNISEL students was classified by using DASS-21 questionnaires. The sample size was suggested at 170 with 90% confidence level. A pilot study was done with 20 respondents and Cronbach’s Alpha test was done to check for questionnaire validity (p<0.05). The outcome was about 22.3%, 38.0%, and 15.2% in severe to extremely severe groups of depression, anxiety, and stress respectively. Significant factors that contributed to OTL related mental health status were the age of respondent, gender, body mass index (BMI), internet connectivity, student’s satisfaction on OTL and MCO challenges influences such as course works, feeling stuck, condition at home, unable to socialize with other and too many responsibilities or chores (p<0.05). In conclusion, this study managed to reveal the impact of OTL due to COVID-19 lockdown which has given a tremendous effect mentally on university students which require immense adaption to new learning technologies and significant investment from universities administrations.